Internal workload in elite female football players during the whole in-season: starters vs non-starters - Romero-Moraleda, Blanca; González-García, Jaime; Morencos, Esther; Giráldez-Costas, Verónica; Moya, José; Ramirez-Campillo, Rodrigo (Biology of Sport, 2023)
The aim of this study was to quantify weekly internal workload across the in-season and compare the workload variables between starter and non-starter Spanish female first league (Liga Iberdrola) football players. Twenty-six participants belonging to the same team (age, height, and mass: 25.4 ± 6.1 years, 167.4±4.8 cm and 57.96±6.28 kg, respectively) participated in this study. Training loads (TL) and match loads(ML) were assessed through breath-cardiovascular (RPE breath ), leg-musculature (RPE leg ) and cognitive (RPE cog ) rating of perceived exertion (RPE0–10) for each training session and match during the in-season phase (35 weeks). Session-RPE (sRPE) was calculated by multiplying each RPE value by session duration (minutes). From these, total weekly TL (weekly TL+ML), weekly TL, weekly ML, chronic workload, acute:chronic workload ratio, training monotony, and training strain were calculated. Linear mixed models were used to assess differences for each dependent variable, with playing time (starter vs non-starter players) used as a fixed factor, and athlete, week, and team asrandom factors. The results showed that total weekly TL(d = 1.23–2.04), weekly ML(d = 4.65–5.31), training monotony (d = 0.48–1.66) and training strain (d = 0.24–1.82) for RPE breath , RPE leg and RPE cog were higher for starters in comparison with non-starters (p = 0.01). Coaches involved in elite female football should consider implementing differentialsRPE monitoring strategiesto optimize the weekly load distribution for starters and non-starters and to introduce compensatory strategies to equalise players’ total weekly load.